Glial neurobiology - Verkhratsky, Alexei; Butt, Arthur
This is the first edition of a textbook providing an accessible introduction to the physiology and pathophysiology of mammalian glial cells. It is written by 2 leading researchers in the field. Through a well-organized progression, the book provides an overview of glial cell function and discusses glial-neuronal interactions with an emphasis on glial influences on neurophysiology. The book is divided into 3 parts: Physiology of Glia, Glial Cells and Nervous System Function, and Glia and Nervous Systems Pathology